2015
DOI: 10.1080/17588928.2015.1083968
|View full text |Cite
|
Sign up to set email alerts
|

A TMS study on the contribution of visual area V5 to the perception of implied motion in art and its appreciation

Abstract: Over the last decade, researchers have sought to understand the brain mechanisms involved in the appreciation of art. Previous studies reported an increased activity in sensory processing regions for artworks that participants find more appealing. Here we investigated the intriguing possibility that activity in cortical area V5-a region in the occipital cortex mediating physical and implied motion detection-is related not only to the generation of a sense of motion from visual cues used in artworks, but also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 68 publications
3
38
0
Order By: Relevance
“…On the one hand, this interpretation is in keeping with the TMS study of Cattaneo et al (2015b), which showed that V5-TMS significantly decreased the perceived sense of motion and, thus, it also significantly reduced the liking of abstract (but not representational) paintings. On the other hand, Cattaneo et al (2015a) showed that rTMS of lateral occipital cortex altered the liking judgments of representational paintings, but not their perceived clearness, suggesting that the role of perceptual areas in aesthetic experience may go beyond simply providing perceptual information.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…On the one hand, this interpretation is in keeping with the TMS study of Cattaneo et al (2015b), which showed that V5-TMS significantly decreased the perceived sense of motion and, thus, it also significantly reduced the liking of abstract (but not representational) paintings. On the other hand, Cattaneo et al (2015a) showed that rTMS of lateral occipital cortex altered the liking judgments of representational paintings, but not their perceived clearness, suggesting that the role of perceptual areas in aesthetic experience may go beyond simply providing perceptual information.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, it should reduce the influence of implied motion on the aesthetic appreciation of all stimuli, with predicted effects for both static and implied motion stimuli. In keeping with this idea, Cattaneo et al (2015b) have recently shown that stimulation of V5, which is involved in processing object motion, interfered with the perception of the sense of motion and with the liking judgments of paintings with various levels of implied motion. Importantly, in the present study, we compared the effects of EBA-and dPMC-rTMS on judgments of models of the same as or of the other gender than that of the observer, thus expanding previous neuroaesthetic works, which instead focused on changes in limb position of a single male dancer (Calvo-Merino et al, 2010), thus possibly masking any effects due to the model's gender.…”
Section: Introductionmentioning
confidence: 90%
“…Response-key assignment was counterbalanced across participants. Note that although previous studies using body shape stimuli presented for less than 200 ms have found reliable liking judgments (e.g., Cazzato, Mele, & Urgesi, 2014, we preferred to maintain paintings visible until response to allow more proper processing of the paintings' content (see also Cattaneo et al, 2015;Cattaneo et al, 2017;Graham, Pallett, Meng, & Leder, 2014; Gerger, Dressler, & Schabmann, 2012). In both tasks, the same 80 artworks (40 portraits and 40 nonportraits) were presented in random order.…”
Section: Methodsmentioning
confidence: 99%
“…Our hypothesis is that deciding about the expressivity of a portrait should recruit the same neural circuits that are involved in processing facial expressions in real individuals (but see Di Dio et al, 2011;Kesner & Horáček, 2017;Lutz et al, 2013) and, therefore, that TMS over face-sensitive sectors of the STS and the SC should affect participants' judgments. Moreover, since (decisions about) liking a painting may rely-at least in parton the same brain regions involved in sensory information processing (Cattaneo et al, 2015;Cattaneo, Schiavi, Silvanto, & Nadal, 2017;Vartanian & Goel, 2004), interfering with STS and SC activity may affect liking beyond expressivity evaluation.…”
mentioning
confidence: 99%
“…The recent use of brain stimulation techniques has produced direct evidence that the appreciation of abstract and representational art relies on different neural mechanisms. For instance, activity in the lateral occipital area contributes more to the appreciation of representational than abstract art (Cattaneo et al, 2015), visual area V5 activity contributes more to the appreciation of abstract than representational art (Cattaneo, Schiavi, Silvanto, & Nadal, 2017), and left prefrontal cortex is related more to the appreciation of representational art than to abstract art (Cattaneo, Lega, Flexas, et al, 2014;Cattaneo, Lega, Gardelli, et al, 2014).…”
mentioning
confidence: 99%